2021
DOI: 10.18343/jipi.26.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Bakteri Endofit sebagai Agens Hayati untuk Mengendalikan Penyakit Blas pada Tanaman Padi

Abstract: Bakteri endofit merupakan salah satu kelompok mikrob yang berpotensi untuk dikembangkan sebagai agensia pengendalian hayati penyakit pada tanaman padi. Bakteri endofit yang diisolasi dari tanaman padi varietas lokal di Jambi telah diteliti mampu mengendalikan penyakit hawar daun bakteri pada tanaman padi. Selanjutnya diteliti potensi bakteri endofit tersebut dalam mengendalikan penyakit blas yang sebabkan oleh Pyricularia oryzae dan pengaruhnya pada produksi padi. Isolat bakteri endofit diuji daya hambatnya te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…The growth of pathogens towards and against the bacteria was observed every day until the seventh day. The formula calculates the inhibition percentage [9]. In vitro growth test of root disease colony diameter on PDA media and TSA media tested for inhibition with endophytic bacteria with a factorial RAL pattern according to [10], the model used is as follows:…”
Section: In Vitro Root Disease Inhibition Test With Endophytic Bacteriamentioning
confidence: 99%
“…The growth of pathogens towards and against the bacteria was observed every day until the seventh day. The formula calculates the inhibition percentage [9]. In vitro growth test of root disease colony diameter on PDA media and TSA media tested for inhibition with endophytic bacteria with a factorial RAL pattern according to [10], the model used is as follows:…”
Section: In Vitro Root Disease Inhibition Test With Endophytic Bacteriamentioning
confidence: 99%
“…This research was also better than research (Aulia Meyuliana et al, 2022) that best equipment was 350 g/ polybag (cattle dirty cleaner) equipment with a value (25.06 cm). Research (Marwan et al, 2021) showed that endophytic bacteria was able to trigger plant height, in rice plant research. (Pradana et al, 2020) reported that tomato plants inoculated with endophytic bacteria were able to significantly increase height of different tomato plants compared to controls.…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…Endophytic microbes are a group of microorganisms that colonize the internal and intercellular spaces of all plant parts but do not cause disease or major morphological changes in the host and can be antagonistic to pathogens. The use of endophytic microbes as biological control agents is very interesting because it is known that endophytic microbes can colonize tissues, produce antimicrobial compounds, and increase tolerance to biotic and abiotic stress [9][10][11].…”
Section: Introductionmentioning
confidence: 99%